Haematologic alterations caused by Ipomoea carnea in experimental poisoning of guinea pig - García, Enrique N. (2015)
Ipomoea carnea subsp. fistulosa (Convolvulaceae) causes poisoning of goats, sheep and cattle in many tropical and subtropical countries. The pathophysiology of this poisoning mainly involves an abnormal glycoprotein metabolism. The aim of this study was to describe the potential toxicity of I. carnea in a guinea pig model through its effect on hematopoiesis in a time course study of 40 days. Experimental poisoning was achieved by feeding animals with "small balls" prepared with milled leaves of I. carnea mixed with commercial crushed pellets for rodents. Hematologic and biochemical parameters, bone marrow and spleencellularities, histopathologic evaluations and lectin-histochemistrywere performed during the scheduled time of the study. The treatment with "small balls" caused significant changes in the weight of spleen, a notable decrease in peripheral red blood cells, and concomitantwith morphological and histopathologicalalterationsin hematopoietic tissues. Overall, the present study suggested that 20 days ofthis treatmentcouldbe enough to develop bone marrow hypoplasia and vacuolation of white cells of spleen, blood and lymph nodes with a transient erythropoietic contribution of the splenic niche. Moreover, this work provides a cheap and simple method for detecting preclinical cases of intoxication by I. carnea in livestock.